National Exam Try Out Application Design At SMP Negeri 35 Makassar - Angraini, Dewi; Ernie C. Avila; Robbi Rahim; Supriadi Sahibu (Ceddi Journal of Education, 2023)
The problem with the current system is that Try Out for the National Examination at SMP Negeri 35 Makassar is still done manually, therefore I provide a solution for designing the Try Out application, which produces an application that can help students in preparation for the National Examination. This research aims to design an effective and efficient national exam try-out application at SMP Negeri 35 Makassar, implementing the Dynamic System Development Method (DSDM) at SMP Negeri 35 Makassar. This data was obtained through literature studies and interviews. Data analysis uses PHP programming scripts and MySQL data. The results of this research show that the Try Out application is user-friendly, has an attractive appearance, and has complete features that can make things easier for students, especially in carrying out Try Outs, so that the process of processing test results is more effective and efficient, the Try Out Application is quite good, useful for users and so needed that it was declared feasible based on the tests carried out, with an average score of 86.00% from 44 respondents.